AB0981 Tendon Involvement in Patients with Gout. an Ultrasound (US) Prevalence Study. (10th June 2014) - Ventura Rios, L.; Cazenave, T.; Audisio, M.; Alva, M.; Mora, C.; Bertoli, A.; Santiago, L.; Solano, C.; Pineda, C.; Hernández-Díaz, C.
Abstract : Background: Chronic gout is characterized by urate monosodium crystals (MSU) deposition in different tissues, mostly in soft tissues and the joints of lower extremities. The prevalence of tendon involvement by gout is not well described Objectives: To examine the prevalence of monosodium urate crystal deposition in lower extremity tendons in patients with gout using high frequency ultrasound Methods: A multicenter, international, descriptive, cross-sectional study in which patients with gout diagnosed by ACR criteria were included to assess the presence of US lesions suggestive of gout (hyperechoic nebulous areas with or without acoustic shadowing, and/or hyperechoic punctuate images [1]) in the quadriceps, patellar and Achilles tendons. US abnormalities were compared to those in a chronic non-microcrystalline condition (osteoarthritis [OA]) and healthy volunteer's tendons. Different US equipments were used; all equipped with linear array probes between 7 to 12 MHz. All individuals underwent a detailed clinical evaluation Results: Seventy seven patients with gout, 35 with OA and 35 healthy subjects were included. Clinical and demographic data of gouty subjects are shown in the table. Mean age was 41.5±7.98 years for healthy subjects. In gouty patients, patellar tendon was involved in 56% (proximal 35 vs distal insertion 22%), quadriceps 44%, and Achilles tendon in 36%. Hyperechoic nebulous areas without acoustic shadowing was the most common form of tendon involvement. The prevalence of tendon abnormalities was greater in the gouty group compared to OA and healthy controls (0.8% vs 0% [p=0.005]). Conclusions: Lower limb tendons are commonly affected in patients with gout. References: Peiteado D, De Miguel E, Villalba A, Ordoñez MC, Castillo C, Martin Mola E. Value of a short full joint ultrasound test for gout diagnosis. A pilot study. Clin Exp Rheumatol 2012;30:830-837 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5720